Affinity purification of erythropoietin from cell culture supernatant combined with MALDI-TOF-MS analysis of erythropoietin N-glycosylation - David Falck (Nature Portfolio, 2017)
Abstract Erythropoietin (EPO) is a heavily glycosylated hormone whose recombinant forms are used for treatment of anaemia. EPO glycosylation is important for its pharmacological properties. An analytical workflow, which can determine EPO glycosylation in an accurate and high-throughput fashion from cell culture supernatant (CCS) in approximately 24 h, offers the possibility to follow changes during production. To address this challenge, we present a complete workflow consisting of protein purification, glycan release, sialic acid derivatization, solid phase extraction, matrix-assisted laser desorption/ionization - mass spectrometry (MALDI-MS) analysis and MassyTools data processing. EPO purification from CCS by anti-EPO antibody coupled Sepharose beads yielded excellent purity with acceptable recovery and was free of glycoform bias. Glycosylation profiles obtained by MALDI-MS were highly comparable to those obtained with an established capillary gel electrophoresis–laser induced fluorescence method. Our method delivers accurate results for the analysis of changes of important glycosylation parameters, such as sialylation and number of N-acetyllactosamine units, for the time course of a fermentation. We could resolve differences in glycosylation between several CCS samples.